Prospective long-term follow-up of autologous chondrocyte implantation with periosteum versus matrix-associated autologous chondrocyte implantation: a randomized clinical trial: - Barié, Alexander; Kruck, Patrizia; Sorbi, Reza; Rehnitz, Christoph; Oberle, Doris Franziska; Walker, Tilman; Zeifang, Felix; Moradi, Babak (The American journal of sports medicine, 2020)
Background: Matrix-associated autologous chondrocyte implantation (MACI) is a further development of the original autologous chondrocyte implantation periosteal...
Gesehen am 24.08.2020